The 1947 Seelisberg Conference: The Foundation of the Jewish-Christian Dialogue - Rutishauser, Christian M. (Studies in Christian-Jewish Relations, 2007)
On the 60th Anniversary of the 1947 International Emergency Conference on Anti-Semitism in Seelisberg, Switzerland, this article provides an overview and analysis of: historical events leading up to this conference; the working process and results of the conference with a focus on the specific work of its various commissions, especially that of Commission III on the Role of the Churches and the Ten Points (Theses) of Seelisberg. Looking back from the present-day vantage point, it comments on the effects of its work over the past several decades, and closes with a brief summary of the 60th Anniversary Jewish-Christian scholarly conference hosted at Lasalle-Haus in Bad Schonbrunn, Switzerland -including the 2007 joint declaration by the Swiss Bishops Conference, the Federation of Swiss Protestant Churches and the Swiss Federation of Jewish Communities. An Addendum to the article provides a photograph and a list of the 1947 conference officers and commission participants.